Inclisiran Lowers LDL-C and PCSK9 Irrespective of Diabetes Status: The ORION-1 Randomized Clinical Trial - Leiter, Lawrence A.; Teoh, Hwee; Kallend, David; Wright, R. Scott; Landmesser, Ulf; Wijngaard, Peter L.J.; Kastelein, John J.P.; Ray, Kausik K. (Diabetes care, 2019)
To evaluate the efficacy and safety of inclisiran by diabetes status. ORION-1 (ClinicalTrials.gov, NCT02597127) randomized 501 subjects with atherosclerotic cardiovascular disease (ASCVD) or ASCVD risk equivalents and high LDL cholesterol (LDL-C), despite maximally tolerated LDL-C-lowering therapies, to one or two doses of placebo or inclisiran. Levels of lipids and proprotein convertase subtilisin/kexin type 9 (PCSK9) at baseline and day 180 were compared. Inclisiran was associated with marked declines in LDL-C (median -28% to -52%, < 0.0001 and -28% to -55%, < 0.005 for all doses in the without- and with-diabetes groups, respectively) and PCSK9. The inclisiran-treated groups also had lower apolipoprotein B, non-HDL cholesterol, and lipoprotein(a) but higher HDL cholesterol. Inclisiran had an adverse profile similar to that of placebo, and adverse events were proportionally balanced in the baseline with- and without-diabetes groups. PCSK9-targeted siRNA-driven strategies may provide a novel therapeutic option for managing dyslipidemia in the presence and absence of diabetes.